Feature-Aware Cooperative Relaying for Multiflow Wireless Sensor Networks - Ming Tao; Huaqiang Yuan; Wenhong Wei; Chao Qu (International Journal of Distributed Sensor Networks)
Addressing the energy efficiency in data-centric and application-oriented wireless sensor networks is an eternal theme, and in the practical scenarios deployed multiple flows, often a serious problem of collisions among multiple paths caused by the fierce network resource competition directly influences the whole network performance. To address this issue, in terms of the delay sensitivity imposed on the deployed flows, a feature-aware cooperative relay selection scheme is developed by comprehensively taking both the routing selection and contention avoidance into account, in which the concept of abstract domain is introduced to extend the covered relay nodes. The optimal relays for the deployed multiflow with specific probing and transmission requirements are selected to find collision-free and energy-efficient cooperative routings. Simulations conducted on NS-2 platform demonstrate that the proposed cooperative routing outperforms the compared routing selection strategies in significantly balancing the energy distribution and prolonging the network lifetime.